Health communication theoretical and critical perspectives - Cross, Ruth; Davis, Sam 1968-; O'Neil, Ivy; Davis, Sams (Cambridge, UK Polity Press, 2017)
Health communication is key to promoting good population and individual health outcomes. As the field has developed, there is a growing need for a critical appraisal of the ideologies and theories underpinning health communication in order to ensure effective practice. This text outlines key issues in the field.
Introduction to health communication : theoretical and critical perspectives -- Communication theory -- Educational theory -- Psychological theory -- Methods and media -- Social marketing -- Health literacy -- Challenges in health communication and behaviour change -- The politics of health communication and behaviour change -- Looking to the future.
Includes bibliographical references and index.
Keywords: Communication in medicine; Health risk communication; Medical informatics